Optimal Capacity Configuration and Day-Ahead Scheduling of Wind-Solar-Hydrogen Coupled Power Generation System - Chengzhen JIA; Lingmei WANG; Enlong MENG; Derong YANG; Dongjie GUO; Yushan LIU (Zhongguo dianli)
In order to realize the optimal capacity allocation and day-ahead scheduling in wind-solar-hydrogen coupled generation system, the NSGA-II intelligent optimization algorithm is used to solve the multi-objective optimization problem of capacity allocation, and the optimal dispatching algorithm considering hydrogen transportation constraint is constructed on power generation side. Firstly, the equivalent mathematic model of each subsystem is established, and the economic indicator combining income and annual average cost of whole life cycle is put forward. Hydrogen production, fuel cell power and hydrogen storage capacity are obtained with the objective functions defined as system abandonment rate, power shortage rate and economy. Secondly, by taking the optimized capacity as the constraint condition of the day-ahead optimal coordinated control model, a single-objective optimization model is established to minimize the planning deviation and variation of pressure of hydrogen storage on the basis of the weighted coefficient method. Finally, the model is simulated and validated in Matlab. Hence the optimal capacity ratio and coordinated optimal control of the system is fulfilled.